Perception of family functioning and personal social networks of university students - Couceiro, Mariana (2022)
This study aimed to analyze the perception that university students have of the functioning of their families, to characterize their personal social network and to study the relations between these variables. The sample consisted of 247 university students, aged between 17 and 55, who completed the Flexibility and Family Cohesion Assessment Scale version IV and the Instrumento de Análise da Rede Social Pessoal. Regarding the results obtained, the students perceived their families as balanced. However, they were dissatisfied with their families. The participants who are with the family more often perceive their families as more enmeshed. The student’s social networks had an average of eight elements and are mainly composed by family and friends. The social networks were cohesive, with a high perception of reciprocity and support. The access to higher education did not generate changes in the size of the social network. There was also an association between network size and family cohesion and flexibility. This study contributes for the comprehension of the family role and social network in the individual, family and social development of students, highlighting the normative challenges. It also contributed to the reflection on possible intervention practices that may prove necessary at this stage.